Kalanchoe tomentosa (Crassulaceae subfam. Cotyledonoideae), a variable, shrubby, and completely tomentose species from Madagascar, with reference to its horticultural derivatives - Smith, Gideon F. (Phytotaxa, 2024)
The Malagasy Kalanchoe tomentosa (Crassulaceae subfam. Cotyledonoideae) is a variable, tomentose, and shrubby species from which numerous morphological variants have been selected as cultivars. Other variants are distributed under monikers presented as cultivar names, but it is likely that at least some of these have not been established as such under the International Code of Nomenclature for Cultivated Plants (ICNCP or Cultivated Plant Code). The monikers therefore variously serve as common names only, or as trade designations, which are not regulated by the ICNCP. Only a few of the established cultivar names, notably K. ×edwardii ‘Fang’ and K. ×edwardii ‘Roseleaf’, were derived from hybrid material of which K. tomentosa, the species itself, therefore, is one parent. An overview is presented of as many as possible of the widely used, established and apparently not established, names usually presented as cultivar names that apply to material derived from K. tomentosa. A large selection of these is illustrated. Three Groups are established under K. tomentosa, based on the predominant colour of the tomentum that cover the ad- and abaxial leaf surfaces. The Groups are: (1) K. tomentosa Silvery White Group; (2) K. tomentosa Reddish Brown Group; and (3) K. tomentosa Greenish Golden Group. One new cultivar is described.